Statistics Training at the University Level: Challenges and Opportunities - Ramos Vargas, Luis Fernando (2019)
The training on statistics is a phenomenon that has sparked great interest in recent years, which is evidenced by the increase in the number of research work at all educational levels. Technological development has brought with it important changes to society and has produced an immense amount of information that grows daily, which is why a different type of citizen and professional is needed; one who is able to understand and interpret the information that surrounds him or her. However, university students show unfavorable attitudes towards statistics, which can be seen in the unsatisfactory results in terms of learning and application. This is a bibliographic-documentary research that examines the elements that take part in the statistical teaching and learning processes at the university level. The exhibition is organized in four parts: the first presents the problems of statistical education in university classrooms; the second explains the cognitive levels involved; the third presents seven teaching models; and the last one examines the implications for the future of statistical education at the university level.